Present situation and future potential of cassava in India - Edison, S. (International Center for Tropical Agriculture, 2001)
Cassava (Manihot esculenta Crantz.) is cultivated in India in about thirteen states (out of 32 states and union territories) with major production in the South Indian states of Kerala (142,000 ha) and Tamil Nadu (65,700 ha). It is now a major industrial crop in Tamil Nadu and is also gaining importance in Andhra Pradesh. The area and production trends of cassava in India and the major constraints to cassava production are highlighted in this paper. The emerging trends in cassava production, like the true cassava seed program, organic manuring, mycorrhizal technology, etc., and the strategy adopted in India to contain cassava mosaic disease, are briefly discussed. The efforts made to popularize high yielding varieties in traditional areas, and to expand cassava cultivation to non-traditional areas where the poverty stricken rural people make up a major share of the population, are also detailed. The transfer of cassava production technology is done through specific outreach programs of the Institute, namely the Lab-to-Land Programme, Institute Village Linkage Programme and Farmers Seminars. A special program, called “Testing and popularising cassava varieties”, is currently undertaken in Tamil Nadu. The production and processing technologies are also transferred through consultancies, as in the case of Project Uptech (in Andhra Pradesh … 21,000 ha of cassava), in which a partnership is established with the State Bank of India. The technological advancement made in the field of cassava utilization and the diversified value-added products that can be made from cassava are described. Realizing the industrial importance cassava is likely to attain in the next 20 years, priorities for future development have been identified. While attempting to augment internal demand by developing and marketing value-added products and increasing the use of cassava in poultry and fish feeds, opportunities for export markets need also to be explored. Some of the imminent problems faced by the cassava starch industry, and efforts being made to address these issues, are narrated. The need for setting up rural agro-enterprises based on cassava as well as organized marketing channels for the roots to ensure a reasonable income for producers, human resource development through international collaboration, the role of participatory research in solving farmers’ problems, etc. are also discussed.